Servqual and service trust as moderation variables in the analysis of user satisfaction in the use of ciputra education digital experience: TAM2 approach - Salim, Ika Raharja; Suryani, Erma (Institute of Computer Science (IOCS), 2023)
The development of Technology 5.0 and the occurrence of COVID-19 have made the implementation of technology a crucial aspect, especially in education, particularly in the data management of higher education institutions. The Research and Community Service Institute of Ciputra University Surabaya has developed and implemented the Ciputra Education Digital Experience (CEdX) information system, but no evaluation has been conducted before. The theory used in this research is the Technology Acceptance Model 2 (TAM2), with the moderating variables of Service Quality (Servqual) and Service Trust. A quantitative research method is employed, with data collection using a questionnaire, and data processing using SMARTPLS 4. Based on 228 collected data, all variables meet validity criteria, with outer loading > 0.6 and fulfilling construct reliability, with Cronbach's alpha > 0.7. In the overall hypothesis testing, 7 hypotheses are accepted, and 9 hypotheses are rejected. The subjective norm variable in this study indicates no influence, possibly due to the SN context being supervisors. Furthermore, output quality and result of demonstrability also have no effect. Service trust is proven not to have a significant influence. Meanwhile, variables that do have an impact show that the ease of use and usefulness of CEdX affect the intention to use CEdX, as evidenced by the p-value of PEU and PU < 0.05. In addition, the quality of the Research and Community Service Institute's services also reinforces and increases faculty members' intention to use CEdX